Early-life obesity and adulthood colorectal cancer risk: a meta-analysis - Harrison Garcia; Mingyang Song (Pan American Health Organization, 2019)
Objective. This meta-analysis examines the relationship between early-life obesity and risk of colorectal cancer (CRC) in adulthood. Methods. A systematic search of Google Scholar, PubMed, and reference data was conducted. Fifteen relevant studies were identified and meta-analyzed, for men and women separately. A random-effects model was used to compare the multivariable-adjusted relative risks (RR) of overall and subsite-specific CRC to the highest versus lowest categories of body mass index (BMI) in early life. Meta-regression was performed on factors that may have contributed to between-study heterogeneity. Results. High early-life BMI was associated with a 39% increased risk of CRC in adult men (RR = 1.39, 95%CI = 1.20 - 1.62, P < 0.0001) and a 19% increased risk of CRC in adult women (RR = 1.19, 95%CI = 1.06 - 1.35, P = 0.004). No statistically significant heterogeneity was identified in meta-regression according to tumor subsite (RR = 1.06, 95%CI = 0.97 - 1.17, RR = 1.08, 95%CI = 0.99 - 1.18 for male and female proximal colon cancer; RR = 1.51, 95%CI = 1.22 - 1.87, RR = 1.08, 95%CI = 0.98 - 1.19 for male and female distal colon cancer; and RR = 1.39, 95%CI = 1.1 - 1.77, RR = 1.51, 95%CI = 0.94 - 2.03 for male and female rectal cancer) or other factors, including age of BMI assessment, self-reported or measured BMI, and adjustment for smoking. Conclusions. The results suggest that high early-life BMI is associated with increased risk of CRC in adulthood. Further studies should investigate adult CRC risk in early-life obese individuals from non-Western countries and the underlying mechanisms by which early-life adiposity may influence CRC pathogenesis.